Pengaruh Motivasi Kerja, Kemampuan Kerja, dan Lingkungan Kerja Terhadap Kinerja Karyawan UD Rahayu Kec. Gurah Kab. Kediri - Rini Wulandari; Moch. Saleh Udin; Taufik Akbar (Universitas Kristen Indonesia Toraja, 2023)
This research aims to find out whether work motivation, work ability, and the work environment have a partial or simultaneous influence on employee performance of UD Rahayu Kec. Gurah District Kediri. Sampling technique in this research, the saturated sample method was used, namely the entire number population of 38 employees. The data source for this research was obtained through observation, interviews, library or literature studies, questionnaires, and dokumentation. Data processing is through the SPSS 21 program. Data analysis techniques used are validity test, reliability test, classical assumption test, regression analysis multiple linear, hypothesis testing, and analysis of the coefficient of determination (R2). The research results show that: (1) Work motivation has a signifiant effect on employee performance, with the t test results obtained a significance value of 0,001 and the calculated t value is 3,473. (2) Work ability has significant effect on employee performance, with the t test results obtained a significance value of 0,009 and the calculated t value is 2,772. (3) The work environment has a significant effect on employee performance, with the t test results obtained a significance value of 0,005 and the calculated t value is 2,966. (4) Work motivation, work ability and work environment has a significant effect on employee performance, with the F test results obtained a significance value of 0,000 and a calculated F of 18,287.